2018
DOI: 10.1039/c8nr03229g
|View full text |Cite
|
Sign up to set email alerts
|

M13 bacteriophage spheroids as scaffolds for directed synthesis of spiky gold nanostructures

Abstract: The spherical form (s-form) of a genetically-modified gold-binding M13 bacteriophage was investigated as a scaffold for gold synthesis. Repeated mixing of the phage with chloroform caused a 15-fold contraction from a nearly one micron long filament to an approximately 60 nm diameter spheroid. The geometry of the viral template and the helicity of its major coat protein were monitored throughout the transformation process using electron microscopy and circular dichroism spectroscopy, respectively. The transform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(45 citation statements)
references
References 79 publications
4
40
1
Order By: Relevance
“…An M13 bacteriophage with a gold-binding peptide, VSGSSPDS, displayed on each of approximately 2700 copies of the pVIII major coat protein found along the viral length was selected and studied as a scaffold for photothermal antibacterial agents. The gold-binding phage was transformed from its filamentous form to its spheroidal polymorph as previously described . Briefly, the phage was dispersed in 100 μL of tris-buffered saline (TBS, 50 mM Tris-HCl, 150 mM NaCl, pH 7.5) at a concentration of 10 8 pfu/μL and vortexed with an equal volume of chloroform (99.8%, ACROS Organics) for 5 vortex/rest (2 s/13 s) cycles at room temperature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An M13 bacteriophage with a gold-binding peptide, VSGSSPDS, displayed on each of approximately 2700 copies of the pVIII major coat protein found along the viral length was selected and studied as a scaffold for photothermal antibacterial agents. The gold-binding phage was transformed from its filamentous form to its spheroidal polymorph as previously described . Briefly, the phage was dispersed in 100 μL of tris-buffered saline (TBS, 50 mM Tris-HCl, 150 mM NaCl, pH 7.5) at a concentration of 10 8 pfu/μL and vortexed with an equal volume of chloroform (99.8%, ACROS Organics) for 5 vortex/rest (2 s/13 s) cycles at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…A segmented line function was used to measure the length and width of the templates. Structures with an aspect ratio between 3 and 25 with lengths between 80 and 300 nm were defined as i-forms, while geometries with aspect ratios <3 were denoted as spheroids …”
Section: Methodsmentioning
confidence: 99%
“…The work described above, as well as a number of publications on TMV SPs and demonstration of their biotechnological potential, arouse interest in SPs based on fi lamentous bacteriophages [1,2,10,58]. A group of scientists from the University of California has published a number of papers on the production and application of M13 SPs, with affi nity to gold [6,55,59]. The intermediate forms and the M13 SPs themselves were covered with gold, and in both cases ability of the particles to act as a photothermally-induced antibacterial agent was shown using the example of Escherichia coli cells.…”
Section: Structurally Modified Bacteriophage Particles and Their Appl...mentioning
confidence: 99%
“… 24 , 25 If such a procedure was followed, gold products should have a linear structure consisting of aggregated gold particles along the rod-like virus. 17 , 18 , 20 However, the gold products in these works were often presented as plate-like or spherical nanoscale particles. 24 , 25 It was proposed that the virus might attach to the surface of the particulate gold particles to stabilize them, whereas Wang’s group observed that discrete gold nanoparticles stood side-by-side with intact filamentous viruses.…”
Section: Introductionmentioning
confidence: 99%
“…Instead of the nonspecific electrostatic interactions of the ionic metal precursors with the virus surface, genetic manipulations of M13 have been explored to fuse the N-terminus of the p8 coat protein with the gold-affinity peptide fragments, which can promote highly efficient bioadsorption of gold ions onto the virus surface. 15 18 Laborious biopanning to screen gold-affinity mutants and constrained accessibility of the genetic techniques and so forth have limited the applications of such genetically engineered viruses. In contrast, chemical modification is a much versatile way to functionalize the M13 virus, thanks to the rich surface chemical groups of the solvent-exposed amino acid residuals of the p8 coat proteins.…”
Section: Introductionmentioning
confidence: 99%